Carnivalesque culture and alcohol promotion and consumption at an annual international sports event in New Zealand. (May 2016) - Gee, Sarah; Jackson, Steven J; Sam, Mike
This study investigated the promotion and consumption of alcohol at the 2012 New Zealand Rugby Sevens Tournament. The paper uses a quantitative survey to gain insight into how attendees experienced the event in relation to alcohol promotions and alcohol consumption. One hundred and six participants completed the survey, the results of which highlight respondents' opinions of: (a) the appearance and role of alcohol promotions at the event; (b) the link between event atmosphere and alcohol consumption; and, (c) messages about moderating alcohol consumption during the event. The discussion draws attention to how live spectators of one particular alcohol-sponsored sports event perceived the role of alcohol as part of the entertainment package and the atmosphere of the event.